PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA PADA DINAS PEMADAM KEBAKARAN KABUPATEN BONE - Edi Jusriadi; Asmina Asmina (Universitas Muhammadiyah Makassar, 2020)
The research method uses quantitative methods with data collection techniques using questionnaires which were distributed to 57 respondents. Data analysis techniques used in this study are multiple linear regression with work safety variables (X1), health variables (X2) and the performance of the State Civil Apparatus (Y). The results showed that work safety variables had a positive and significant effect on the performance of the State Civil Apparatus in the Bone Fire Service with t count 3.828 t table 2.002 with a significance level of 0.000 0.005, the effect of occupational health had a positive but not significant effect with a t value of 1.667 t table 2,002 with a significance level of 0.099 0.05.